2019
DOI: 10.1111/eip.12832
|View full text |Cite
|
Sign up to set email alerts
|

Views of young people in Malaysia on mental health, help‐seeking and unusual psychological experiences

Abstract: Aim: Mental health problems are prevalent among young people in Malaysia yet access to specialist mental health care is extremely limited. More context-specific research is needed to understand the factors affecting help-seeking in youth, when mental health problems typically have first onset. We aimed to explore the attitudes of vulnerable young Malaysians regarding mental health problems including unusual psychological experiences, help-seeking and mental health treatment.Methods: In the present study, nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…A diagnosis of mental health issues was shown as a risk to reputation (Berry et al, 2019). Furthermore, family members avoided discussion on this topic if any of the relatives had a mental health problem (Chang & Horrocks, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A diagnosis of mental health issues was shown as a risk to reputation (Berry et al, 2019). Furthermore, family members avoided discussion on this topic if any of the relatives had a mental health problem (Chang & Horrocks, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The 25 studies (Abdul Kadir & Bifulco, 2010; Abdullah et al, 2016; Berry et al, 2019; K. S. Chen & Kok, 2017; Chu et al, 2018; Edman & Koon, 2000; Fernandez et al, 2016; Hanjeet et al, 2007; Ibrahim et al, 2019; Jacob et al, 2015; Keng, 2005; Khan, Sulaiman, et al, 2009; Khan, Syed Sulaiman, et al, 2009; Khan et al, 2010; Loo & Furnham, 2012, 2013; Loo et al, 2012; W. Y. Low et al, 1995, 1996; H. M. Low & Zailan, 2018; Shoesmith et al, 2018; Swami et al, 2008, 2010; Yeap & Low, 2009) mentioned mental health knowledge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few factors that have become the barrier to these types of services according to Berry et al (2020). In studies that were conducted in Malaysia, counselling assistance that involve adult mental health patients or those with an unknown age is limited.…”
Section: Problem Statementmentioning
confidence: 99%
“…This situation has caused teenagers and school students to always be at risk of being exposed with the activity of substance abuse. Berry et al (2020) stated that finding help is classified as an acting agent, involving an active process of seeking help and becoming spontaneously ready and active in facing their problems. Participants in this study had confirmed psychological therapy to be potentially effective in enhancing overall wellness and overcoming certain problems.…”
Section: Introductionmentioning
confidence: 99%